1985
DOI: 10.3109/00016348509154702
|View full text |Cite
|
Sign up to set email alerts
|

BETA‐THROMBOGLOBULIN (β‐TG) AND PLATELET FACTOR 4 (PF4) IN OBSTETRICAL CASES

Abstract: The plasma levels of beta-Thromboglobulin (beta-TG) and Platelet Factor 4 (PF4) were measured in patients during the normal obstetrical period and in pre-eclampsia. A significant increase was observed in the two proteins with respect to the non-pregnant control group but no difference was seen between pregnancy and puerperium in either the normal or pre-eclamptic cases. The one significant variation in the concentration of the two proteins was a sharp rise during parturition. There was no correlation between b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…[16][17][18][19] This supports the occurrence of platelet activation in vivo during the later stages of pregnancy. Interestingly, Douglas et al showed that the increased levels of beta-TG in pregnancy were not associated with an increase in fibrinopeptide A, a marker of thrombin generation.…”
Section: Bttu-thromhorlobulin and Platelet Factorsupporting
confidence: 65%
“…[16][17][18][19] This supports the occurrence of platelet activation in vivo during the later stages of pregnancy. Interestingly, Douglas et al showed that the increased levels of beta-TG in pregnancy were not associated with an increase in fibrinopeptide A, a marker of thrombin generation.…”
Section: Bttu-thromhorlobulin and Platelet Factorsupporting
confidence: 65%
“…Moreover, the inverse relationship between the mean platelet volume and the platelet count observed during normal pregnancy led to the proposal that pregnancy is a state of compensated thrombocytolysis [129]. There are inconsistent reports concerning the degree of platelet activation and the release of vasoactive products during normal pregnancy [8,51,60,113,114]. Women who develop obstetric complications, such as preeclampsia and fetal growth restriction, have a higher degree of platelet activation than both normal pregnant and non-pregnant women [1,9,11,13,38,48,50,59,62,64,65,74,75,82,86,88,96,99,102,108,116,128,137]; however, little information is available regarding the association between maternal platelet activation and preterm labor (PTL) [117].…”
Section: Introductionmentioning
confidence: 99%